SEJARAH BERDIRINYA PARTAI BARU PASCA REFORMASI DALAM PRESPEKTIF RATIONAL CHOICE : STUDI KASUS PARTAI DEMOKRAT - ABDULLOH, ZUNAIDI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
There are some academicians who conducted research on the emergence of new parties in the post-reform of Indonesia. Their approach generally uses a sociological approach. There is also that use a comparative approach (comparative perspective). Those approaches are less satisfactory to explain the establishment of political parties in postreform of Indonesia. This thesis will present a new perspective which is more satisfactory in view on the emergence of political parties in post-reform of Indonesia. In this research, author analyzes the emergence of the Democratic Party in post-reform of Indonesia by using rational choice approach. The results of this study show, the Democratic Party was founded based on the decision of the founders when they calculate the significant of potential supports for the new party and the main character to be president and charges for support (voice), such as the cost of setting up the party and campaign costs, cheaper than the use of voices when obtained voices have been converted into seats. The decision of establishing a new party which also viewed by the founder of the Democratic Party is cheaper and more profitable than the carrying Susilo BambangYudhoyono, which has potential voters, backed by another party in the 2004 president election.